Experimental and DFT studies on corrosion protection performance of epoxy/graphene quantum dots@TiO2 nanotubes coatings. (7th March 2022) - Ji, Xiaohong; Seif, Abdolvahab; Duan, Jizhou; Rashidi, Alimorad; Zhou, Ziyang; Pourhashem, Sepideh; Mirzaee, Majid; Zhai, Xiaofan; Zhao, Xia; Hou, Baorong
Highlights: Nanohybrids of graphene quantum dots and TiO2 nanotubes (GQD:TNT of 1:0.5, 1:1, 1:2) are synthesized. GQD@TNT nanohybrids are chemically modified with silane (S-H). Solvent-borne epoxy coatings loaded with 0.3 wt% S-H are prepared. Epoxy/S-H (1:1) show the highest corrosion resistance in NaCl solution. Energetics and interaction mechanisms at interfaces is studied by DFT simulation. Abstract: In this paper, the nanohybrids of graphene quantum dots and TiO2 nanotubes (GQD@TNT) with different GQD:TNT weight ratios of 1:0.5, 1:1, and 1:2 are synthesized which are abbreviated as H (1:0.5), H (1:1), and H (1:2), respectively, and further modified with 3-(aminopropyl) triethoxysilane. Then, the silane-modified nanohybrids are loaded at 0.3 wt% in the solvent-borne epoxy matrix to achieve anti-corrosion nanocomposite coatings on the steel substrates. The results reveal that the coatings loaded with silane-modified H (1:1) more effectively enhance the corrosion protection efficiency of the polymer coatings, which has a low-frequency impedance modulus of 5.64 × 10 9 Ω·cm 2 even after 90 days of immersion in the 3.5 wt% NaCl solution. Moreover, the density functional theory (DFT) method is performed to explore the energetics and the interaction mechanisms at each interface. The results imply that the strong adhesions observed at each interface would twist and increase the diffusion path of the corrosive agents, and consequently, retard the electrochemical corrosion reactions at the surface of the metal. Therefore, the proposed strategies could be successfully applied for the development of long-term anti-corrosion coatings.